Optimalisasi Produksi Konten Kreatif pada Media Sosial Tiktok Garuda Systrain Interindo - Arya Rizqi Muhardillah; Hari Otang Sasmita; Mulyono Mulyono (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the optimization of creative content production on the TikTok platform of Garuda Systrain Interindo, a company engaged in occupational safety and health (K3) certification services. The research aims to (1) identify how the content production process is optimized and (2) examine how such optimization improves the effectiveness of creative content based on the principles of Integrated Marketing Communication (IMC). Using a qualitative descriptive approach, data were collected through observation of the company’s TikTok content, documentation, and analysis of content performance indicators. The results show that the optimization process includes structured planning through content planning sheets, determination of content pillars, talent briefing, consistency in editing style, and template standardization. These efforts are supported by post-production activities such as scheduling, performance monitoring, and evaluation through TikTok Analytics. Furthermore, the optimization significantly enhances content effectiveness, as indicated by increased engagement, reach, and stable performance of educational content. The implementation of IMC particularly in terms of message consistency, visual uniformity, and brand identity integration strengthens brand awareness and improves the clarity of K3 educational messages delivered to audiences. Overall, optimized and IMC-based content production contributes to more effective digital communication and strengthens the company’s professional image on social media.